Influências do quadro litoestrutural e dos processos fluviais na configuração do modelado do relevo no Médio Paraguaçú/Jiquiriçá, Região de Milagres/Itatim - BA - João Henrique Moura Oliveira (2020)
The morphogenesis of semi-arid landscapes in Brazil has traditionally been explained by focusing on morphoclimatic aspects, following the pediplanation model. Currently, geomorphological research acquires a new perspective in understanding the genesis and evolution of the relief considering the structural or morphostructural aspects. The State of Bahia served as a great laboratory in the development of geomorphological research from the morphoclimatic perspective, lacking studies that pay attention to structural factors. For this purpose, a sector of located in the Paraguaçu river basin on its right bank at the height of its middle course (area of occurrence of Campos de Inselbergues de Milagres-Itatim-Iaçu). The study area extends to sectors of the divider with the middle Jiquiriçá river basin. Thus, the objective was to analyze the morphogenetic configuration of the modeled from the conditioning of the lithostructural framework and fluvial processes in the Middle Paraguaçu / Jiquiriçá region of Milagres/Itatim - BA. Digital elevation model data of 30 m (DEM-SRTM) and 12.5 m (ALOS-PALSAR) of spatial resolution were used to obtain altimetry, slope, and shaded relief. Also used were medium and high-resolution satellite images, on-site analysis, analysis of rocks by X-ray diffraction (XRD), interpretation of swath profiles, morphometric index: Watershed asymmetry factor, Form factor. First, a geomorphological characterization was carried out, where 5 (five) Units were distinguished in the Paraguaçu Basin sector, and 2 (two) in the Jiquiriçá Basin: Maracás Plateau and Middle Jiquiriçá-Verde Plateau. The structural conditioning of the drains and forms of relief, more specifically inselbergues and marginal mountain ranges, was identified and demonstrated through description and directional analysis. It was identified that both are conditioned to the pattern of compressional shear zones (WNW-ESE), mylonitic zones (NNW-SSE; E-W), fracture lines (NNW-SSE; NNE-SSW) and, locally, the structural lines. The influence of morphostructure and the role of rivers in the morphogenesis of the Paraguaçu Depression was demonstrated through the analysis of longitudinal profiles, where knickpoints. This was corroborated by the identification in the Paraguaçu/Ribeirão-Verde divider, of morphological and topological imbalances using χ-maps and χ-plots analysis, and anomalous drainage features such as elbows, suspended valleys. The geomorphic indexes proved the degree of evolution and dissection of the sub-basins of Paraguaçu in relation to the basins of Ribeirão and Verde. The mapped inselbergs demonstrated a variety of types and evidenced their structural conditioning in relation to geological structures and lineaments. The analysis of rocks via XRD showed a mineralogical difference between rocks of the inselbergues, slabs (Depression) and escarpment. Inselberg rocks are richer proportionately in potassium minerals; the Lajedos rocks have lower K-feldspar values and higher proportions of sodium minerals (Plagioclases). Finally, an evolutionary synthesis of the study area was proposed, where the tributary drainage of the Paraguaçu River, positioned at the height of what currently constitutes the Middle Paraguaçu Depression, began to dissect a mantle of alteration originated in a humid climatic phase. The genesis, depth and expansion of this alteration front was conditioned by the difference between the fracture web and lithological variation of the rocky blocks that would constitute the inselbergs and the erosive surface substrate. As the regolith was denuded, the landscape started to be constituted. Successive phases of this morphogenesis are now perceptible in inselbergs, where epigenic paleosurfaces and tafoni are the main markers of the various evolutionary phases recognizable in the Depression Landscape of the Middle Paraguaçu. It is concluded, therefore, that the inclusion of structural and morphostructural aspects were fundamental for the understanding of landscape.